MODEL OF INTERCULTURAL RECEPTION IN TRADE - SN Maksum (IJED: International Journal of Economy Development Research, 2023)
This study aims to understand how traders engage in social interactions at Besuki Public Market. This is important because such interactions foster attachment that contributes to a comfortable market atmosphere. This research uses a qualitative method with a phenomenological approach. In the analysis, the researcher conducted participant observation, documentation, and structured interviews with traders, buyers, and the market manager. The Intercultural Reception interaction at the market is examined in two aspects: 1) The construction of interaction at Pasar Umum Besuki. 2) The Intercultural Reception behavior formed at Besuki Public Market and its alignment with Islamic values. The findings of this study indicate that: 1) The construction of Intercultural Reception interaction at Besuki Public Market is divided into three interaction patterns: Dominance, Negotiation, and Opposition. These patterns are part of power dynamics that are susceptible to conflicts and continuously shift according to the desires of individuals/groups. 2) In Intercultural Reception, there are cultural values that prevent conflicts, namely: Tasamuh, Ta'awun, and Silaturahmi. These values are embodied in behaviors/activities that respect differences, mutual assistance in trading culture, and fostering good relationships. The Intercultural Reception interaction at the market aligns with Islamic values, considering the cultural/traditional values at the market, which are also Islamic teachings related to social interactions and are often practiced outside of trading activities. However, they have become binding values due to their frequent practice by the same individuals, even if in different times/places.